In-Season Match Demands Of Men’s Collegiate Soccer: A Comparison By Half, Position, Match Outcome, Match Location, And Competition Phase - Richard Aziz; Margaret T. Jones; Andrew R. Jagim; Mary Kate Feit; Nicholas Kuhlman Kuhlman; Thomas Crabhill; Jennifer B. Fields (International Journal of Strength and Conditioning, 2023)
The purpose of this study was to quantify athlete external workload by half, position, match outcome, match location, and competition phase (e.g., conference vs non-conference) during match play across a men’s NCAA DIII soccer season. Throughout the competitive season, 16 soccer players wore a GPS device in 17 matches. Workload metrics collected were: total distance (TD), distance per minute (D/min), distance in speed zones (SZ) 1-5, sprint efforts, sprint distance (SD), top speed, accelerations, player load (PL), and player load per minute (PL/min). TD (4164±1235 m), PL (169±52 AU) D/min (116±20 m/min), PL/min (4.7±0.8 AU), SD (80±55 m), accelerations (32±14), decelerations (35±14), PP (30±10), SZ2 (1520±469 m), and SZ3 (582±222 m) were significantly higher in the 1st half of play. Forwards demonstrated significantly higher top speeds (9.5±2.0 m/s) than midfielders (8.0±1.1 m/s) and defenders (7.7±1.2 m/s). PL (309.45±83.86 AU), D/min (216.82±59.26 m/min), PL/min (8.76±2.26 AU/min), top speed (15.82±3.41 m/s), SZ3 (1059.45±403.27 m) and SZ4 (139.52±75.78 m) were significantly greater in matches that resulted in wins. However, SZ5 (20.59 ± 23 m) was significantly greater during matches that resulted in losses. PL (321.73±93.38 AU), D/min (229.26±74.58 m/min), PL/min (9.24±2.84 AU/min), top speed (16.03±4.43 m/s), SZ2 (2819.48±891.09 m), SZ3 (1130.63±460.09 m), SZ4 (150.33±80.52 m) SZ5 (20.84±22.86 m) were significantly greater during home matches. PL (321.85±88.79 AU), D/min (228.2±64.66 m/min), PL/min (9.16±2.45 AU/min), SZ2 (2850.53±795.83 m), SZ3 (1145.27±456.34 m), and SZ4 (142.49±74.89 m), were significantly greater during nonconference matches. SZ5 (19.23 ± 22.87 m) was significantly greater during conference matches. Match workloads help coaches identify physical demands needed to compete. Tailoring training and monitoring accumulated fatigue will allow coaches to optimize team performance.